The use of procedural sedation in children - Alotaibi, Badriyah (2016)
The use of sedation for diagnostic and therapeutic procedures in children is common and leads to considerable debate. Evaluating this subject is complicated by differences in the methods and the outcomes used for sedation assessment in children reported in the literature which are large. This thesis used systematic literature reviews, a prospective study and a national survey to evaluate several aspects of paediatric sedation.